Extractive Content and Colour Properties of 11-Year-Old Superior Teak Wood - Ganis Lukmandaru; Alfian Nur Falaah; Tomy Listyanto; Dian Rodiana (Masyarakat Peneliti Kayu Indonesia, 2021)
There is a lack of understanding about the properties of fast-growing teak trees harvested in young stage. Superior teak woods (11 years, 5 trees) grown in Pemalang FMU were assessed in vertical and radial positions for its extractive contents and colour properties. Extractions were conducted using a sequence of toluene, ethanol, and hot water. The color evaluation was performed using CIEL*a*b*’s chromaticity system. Toluene-, ethanol-, hot-water-, and total extractive contents ranged between 1.16 5.00%; 0.29 1,04%, and 0.98 2.35%, and 4.03 7.31%, respectively. For color properties, the brightness (L*), redness (a*), and yellowness (b*) indices ranged from 49.50 57.42, 6.08 10.81, and 20.47 25.74, espectively.Toluene- and total extractive contents were greater in heartwood than in sapwood, while the reverse occurred for the hot-water extractive content. Toluene- and total extractive contents were higher in outer heartwood than in inner heartwood. With regard to colour properties, L* and a* values were significantly differed between sapwood and heartwood. Vertical stem analysis of samples obtained at bottom, center, and top showed the toluene extractive content, total extractive content, and a* levels of center part of the tree were found to be lower than other parts. The L* were negatively correlated with extractive contents, with the highest correlation degree (-0.83**) being observed in the total extractive content in the heartwood. It is also noticed that superior teak wood wood was less darker and extractive contents than the heartwood control of a 72-year-old tree. Therefore, the properties measured in the present work might be related with natural durability of the woods.